Enhancing Pronunciation Skills Through Phonetic Method - Nurmahyuni Asrul; Azizah Husda (STAI Hubbulwathan Duri, 2022)
This paper aims at stressing current issue on how to enhance pronunciation skills through the phonetic method. The design applied action research in a classroom where there are two cycles conducted after primarily doing pre-cycle. The techniques to collect the data were an oral test, interviews with students and teacher, and field notes. The findings showed that the first cycle did not significantly enhance students’ skills in pronunciation because, among 24 students, 16 students passed the test with the category of a good score and sufficient. Some students were still confused with the pronunciation instruction and failed to test underscore 60. Thus, It needs the second cycle to reach the goal of the research. The second cycle pointed out that 19 students enhanced their pronunciation skills. This research furthermore gives some contribution. First, the students will have the confidence to use English without any affection to be awkward, nervous through having an interaction with each other and make them able to communicate well. Then, in language learning, it provides both practical and theoretical teaching ideas to the prospective teachers to help and to assess their students for enhancing accurate pronunciation.